Inequity in access to oral health service of primary students: A case study of a dental fund in a central region province - Pothidee T. (2017)
© 2016 Kasetsart University Inaccessibility to services and the prevalence of oral health problems in the school-age children group is consistently increasing and has become a major driver to establish a dental fund since the 2011 fiscal year with productive indicators to increase accessibility to oral health service as the major strategy of the fund. Therefore, the purpose of this study was to investigate equity in the accessibility to oral health promotion and prevention based on this fund. Thus, the research questions formed were whether or not the mechanism of a dental fund has created equity in the accessibility to services of the students and what is the consequence of the funding operation? This study used ethnographical research in a small province in the central region of Thailand and was conducted from May 2012 to January 2013. The key informants consisted of 8 dentists and 14 dental hygienists. The research methods were in-depth interviews, observations, and group discussions. Content analysis was applied and the results were considered based on the concept of health equity. The research findings showed that though the operation had been successful based on the productive indicators of the dental fund, inequity in oral health service provision for school-age children still existed in the research area. Only 20 percent of the students in the suburban area received complete dental treatment which was lower than the target indicator, while more than 20 percent of the students in the district town received the service. Since the operation aimed to achieve the productive indicator, this resulted in dental personnel selecting only the less problematical group of students from the large-sized schools to be able to achieve the indicator easily. Moreover, the procedure indicator findings showed that the goal of having participation from the District Health Coordinating Committee (DHCC) was not achieved in developing oral health promotion and prevention for grade 1 students because the DHCC deferred to the knowledge and expertise of the dentists who still operated based on bio-medicine. As a result, the present work plan and methods for organizing activities with the student group are still emphasizing a full mouth examination and complete treatment according to the quantitative indicator only, without any new approaches or operational concepts.